A review of thermoelectric power generation systems: Roles of existing test rigs/ prototypes and their associated cooling units on output performance. (15th October 2018) - Alghoul, M.A.; Shahahmadi, S.A.; Yeganeh, Bita; Asim, Nilofar; Elbreki, A.M.; Sopian, K.; Tiong, S.K.; Amin, N.
Highlights: Thermoelectric power generation systems are reviewed. Various configurations of test rigs and prototypes are compared and discussed. Factors that influencing the output performance are given. Heat pipe technologies show promising results in heat extraction and passivation. Active cooling technologies are the most dominant method for power generations. Abstract: Thermoelectric technology is a promising solution to recover waste heat from different resources. There are numerous researches in the literature that measure performance of thermoelectric modules (TEMs). A comprehensive review of research studies that classifies and expounds disparities between various thermoelectric power generation (TEPG) systems is still unavailable and therefore, this paper reviews major concerns on their designs and performances. Firstly, various main elements of TEPG systems, which affect the output power of TEMs such as stabilizer or heat exchanger, interface, contact pressure, insulation, cooling system, and integrity are studied. Secondly, performances of test rigs and various prototypes are reviewed in detail based on their cooling methods since cooling is the most prominent factor among other counterparts. In general, the cooling unit is divided into either passive or active cooling system, which is selected based on its well-defined use. A comprehensive study on various test rigs with active cooling systems is given while a broader range in prototypes is covered and classified under detailed surveys. This review is expected to be of value for researchers in the field of thermoelectric. Overall, in order to have a prospective future towards commercialization of TEPG systems, the existing prototypes in the literature are still subjected to many enhancements in their design aspects, while further improvements are needed to be achieved independently in TEMs' development.